Frequency domain interferometry mode observations of PMSE using the EISCAT VHF radar - P. B. Chilson; S. Kirkwood; I. Häggström (Annales Geophysicae, 2000)
During the summer of 1997 investigations into the nature of polar mesosphere summer echoes (PMSE) were conducted using the European incoherent scatter (EISCAT) VHF radar in Norway. The radar was operated in a frequency domain interferometry (FDI) mode over a period of two weeks to study the frequency coherence of the returned radar signals. The operating frequencies of the radar were 224.0 and 224.6 MHz. We present the first results from the experiment by discussing two 4-h intervals of data collected over two consecutive nights. During the first of the two days an enhancement of the FDI coherence, which indicates the presence of distinct scattering layers, was found to follow the lower boundary of the PMSE. Indeed, it is not unusual to observe that the coherence values are peaked around the heights corresponding to both the lower- and upper-most boundaries of the PMSE layer and sublayers. A Kelvin-Helmholtz mechanism is offered as one possible explanation for the layering structure. Additionally, our analysis using range-time-pseudocolor plots of signal-to-noise ratios, spectrograms of Doppler velocity, and estimates of the positions of individual scattering layers is shown to be consistent with the proposition that upwardly propagating gravity waves can become steepened near the mesopause. Key words: Ionosphere (polar ionosphere) · Meteorology and Atmospheric Dynamics (middle atmosphere dynamics) · Radio Science (Interferometry)